Forbidden Fashions : Invisible Luxuries in Early Venetian Convents - Campagnol, Isabella (Book collections on Project MUSE., 2014)
"Form-fitting dresses, silk veils, earrings, furs, high-heeled shoes, make up, and dyed, flowing hair. It is difficult for a contemporary person to reconcile these elegant clothes and accessories with the image of cloistered nuns. For many of the some thousand nuns in early modern Venice, however, these fashions were the norm. Often locked in convents without any religious calling--simply to save their parents the expense of their dowry--these involuntary nuns relied on the symbolic meaning of secular clothes, fabrics, and colors to rebel against the rules and prescriptions of conventual life and to define roles and social status inside monastic society. Calling upon mountains of archival documents, most of which have never been seen in print, Forbidden Fashions is the first book to focus specifically upon the dress of nuns in Venetian convents and offers new perspective on the intersection of dress and the city's social and economic history."--